The impact of histology on recurrence patterns in esophageal cancer treated with definitive chemoradiotherapy. Issue 2 (August 2017) - Xi, Mian; Xu, Cai; Liao, Zhongxing; Hofstetter, Wayne L.; Blum Murphy, Mariela; Maru, Dipen M.; Bhutani, Manoop S.; Lee, Jeffrey H.; Weston, Brian; Komaki, Ritsuko; Lin, Steven H.
Abstract: Background: To assess the impact of histology on recurrence patterns and survival outcomes in patients with esophageal cancer (EC) treated with definitive chemoradiotherapy (CRT). Methods: We analyzed 590 consecutive EC patients who received definitive CRT from 1998 to 2014, including 182 patients (30.8%) with squamous cell carcinoma (SCC) and 408 (69.2%) with adenocarcinoma. Recurrence pattern and timing, survival, and potential prognostic factors were compared. Results: After a median follow-up time of 58.0 months, the SCC group demonstrated a comparable locoregional recurrence rate (42.9% vs. 38.0%, P = 0.264) but a significantly lower distant failure rate (27.5% vs. 48.0%, P < 0.001) than adenocarcinoma group. No significant difference was found in overall survival or locoregional failure-free survival between groups, whereas the SCC group was associated with significantly more favorable recurrence-free survival ( P = 0.009) and distant metastasis-free survival ( P < 0.001). The adenocarcinoma group had higher hematogenous metastasis rates of bone, brain, and liver, whereas the SCC group had a marginally higher regional recurrence rate. Among patients who received salvage surgery after locoregional recurrence, no significant difference in survival was found between groups ( P = 0.12). Conclusions: The patterns and sites of recurrence, survival outcomes, and prognostic factors were significantly different between esophageal SCC and adenocarcinoma.